Evaluation of the effectiveness of chinese acupuncture in pain relieving following surgical removal of Impacted lower third molars - خليل, علي; حمشو , رامز سامر (Latakia University Journal -Medical Sciences Series, 2022)
Surgical extraction of the impacted lower third molar causes severe pain, swelling and inconvenience to the patient. The common treatment for pain is the use of NSAIDs. But these drugs are associated with undesirable side effects. Acupuncture physical therapy can provide effective pain relief without side effects ObjectiveThe number of sample members was 10 patients from the Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Tishreen University, who had impacted lower third molars on both sides, and they were divided into two groups. Experimental group where acupuncture treatment was applied for 30 minutes before starting the surgical extraction of the impacted lower third molars, where the dice method was adopted, where the even number represents the molars to be applied with Chinese needles after their extraction, while the odd number represents the molars in the control group. Pain was assessed using a standardized questionnaire containing information about the patient. Patients were asked to rate the intensity of the pain at the following intervals: after 4, 6, and 12 hours and on the second, third, fourth, fifth, sixth and seventh days 7 Results: The values ​​of pain intensity in the puncture group were lower and statistically significant in the periods after 4 hours and on the second to sixth day Conclusion: Acupuncture physical therapy can relieve postoperative pain after surgical extraction of the affected lower third molars.